Autres methodes de recensement aerien du betail - Grimsdell, J.J.R.; Bille, Jean-Claude; Milligan, K. (CIPEA, 1986)
Discusses six alternative methods for estimating livestock populations based on aerial surveys, mentioning two main factors which affect the resulting population estimates, particularly sampling fraction and the degree of aggregation or clumping of the population being sampled.